2017
DOI: 10.1186/s12906-017-1763-7
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal treatment using curcumin supplements to amend the damage in VPA-induced rodent models of autism

Abstract: BackgroundValproic acid (VPA) is used as a first-line antiepileptic agent and is undergoing clinical trials for use as a treatment for many disorders. Mothers undergoing VPA treatment during early pregnancy reportedly show increased rates of autism among their offspring. The benefits of curcumin supplementation were investigated using an animal model of VPA-induced autism.MethodsThe study was performed using a rodent model of autism by exposing rat fetuses to valproic acid (VPA) on the 12.5th day of gestation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…The animal model of autism induced by VPA is described in the literature as an alternative to investigate behavioral and biochemical changes in rodents similar to those found in individuals with ASD (Mabunga, Gonzales, Kim, Kim, & Shin, 2015). In our study, VPA was administered orally in pregnant rats and the behavioral changes of the pups were similar to those described in other studies when VPA was administered intraperitoneally (Al‐amin et al, 2015; Al‐askar, Bhat, Selim, Al‐Ayadhi, & El‐Ansary, 2017; Bambini‐Junior et al, 2014; Schneider & Przewłocki, 2005). The possible mechanisms involved in VPA‐induced autism‐like behavior in rats include oxidative damage in fetal brain, inhibition of histone deacetylase (promoting increased neuronal death of rat embryos by apoptosis), and imbalance of the GABAergic inhibitory/excitatory system mainly in the hippocampus, generating epileptic seizures and hyperserotonemia (Mabunga et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…The animal model of autism induced by VPA is described in the literature as an alternative to investigate behavioral and biochemical changes in rodents similar to those found in individuals with ASD (Mabunga, Gonzales, Kim, Kim, & Shin, 2015). In our study, VPA was administered orally in pregnant rats and the behavioral changes of the pups were similar to those described in other studies when VPA was administered intraperitoneally (Al‐amin et al, 2015; Al‐askar, Bhat, Selim, Al‐Ayadhi, & El‐Ansary, 2017; Bambini‐Junior et al, 2014; Schneider & Przewłocki, 2005). The possible mechanisms involved in VPA‐induced autism‐like behavior in rats include oxidative damage in fetal brain, inhibition of histone deacetylase (promoting increased neuronal death of rat embryos by apoptosis), and imbalance of the GABAergic inhibitory/excitatory system mainly in the hippocampus, generating epileptic seizures and hyperserotonemia (Mabunga et al, 2015).…”
Section: Discussionsupporting
confidence: 88%
“…Few studies revealed the increase in oxidative stress due to deficiency of antioxidants lead to anxiety and low exploratory activity in rodents (Desrumaux et al, 2005; de Oliveira et al, 2007). The excitotoxicity or release of glutamate is considered one of the primary reasons for generation of reactive species and to disrupt the glutathione homeostasis in (brain and plasma) both VPA‐rodent model and clinical subjects (Al‐Askar et al, 2017; El‐Ansary, 2016). Therefore, oxidative stress has been linked to ASD and undoubtedly played a significant role in its etiology.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, curcumin up-regulated the expression of neurons in hippocampal DG and CA3 regions and down-regulated the expression of astrocytes (48). On the other hand, Al-Askar et al demonstrated that postnatal curcumin treatment reversed various impaired parameters (i.e., IFN-γ, serotonin, glutamine, GSH, glutathione S-transferase, lipid peroxidase, CYP450, IL-6, glutamate, and GSSG) in the VPA model (49). Especially, curcumin improved delayed maturation and abnormal weight (49).…”
Section: Curcuminmentioning
confidence: 99%